HISTORICAL ANALYSIS OF THE ROLE OF UZBEKISTAN IN THE SECOND WORLD WAR - Rafael T. Gilyajdinov; Anzor А. Meiliev (Journals Park Publishing, 2024)
The article analyzes the role and place of Uzbekistan in the Second World War. Uzbekistan, as part of the Soviet Union, played a significant role in this conflict, contributing both on the front and on the home front. The article covers the historical context of the war, the mobilization efforts of the republic, the participation of the Uzbek population in hostilities, as well as the economic and production contribution of Uzbekistan to the overall victory. Particular attention is paid to Uzbek diplomats and politicians who actively participated in the formation of the international coalition against fascism. The consequences of Uzbekistan's participation in the war for its economy, culture and society are also analyzed, emphasizing the importance and contribution of the republic to the overall victory over Nazism.
Keywords: Uzbekistan, World War II, victory, participation, mobilization, economic contribution, cultural heritage, social changes